2015
DOI: 10.5056/jnm14117
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled, Multi-center Trial: Comparing the Safety and Efficacy of DA-9701 and Itopride Hydrochloride in Patients With Functional Dyspepsia

Abstract: Background/AimsTherapies of functional dyspepsia (FD) are limited. DA-9701 is a novel prokinetic agent formulated with Pharbitis semen and Corydalis Tuber. We aimed to assess the efficacy of DA-9701 compared with itopride in FD patients. MethodsPatients with FD randomly received either itopride 50 mg or DA-9701 30 mg t.i.d after a 2-week baseline period. After 4 weeks of treatment, 2 primary efficacy endpoints were analyzed: the change from baseline in composite score of the 8 dyspeptic symptoms and the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 29 publications
3
43
1
1
Order By: Relevance
“…Abdominal bloating occurred in two patients, but this did not significantly affect their appetite, food intake, or quality of life. Previous studies also showed a good safety profile, similar to our results …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Abdominal bloating occurred in two patients, but this did not significantly affect their appetite, food intake, or quality of life. Previous studies also showed a good safety profile, similar to our results …”
Section: Discussionsupporting
confidence: 92%
“…One tablet of 30‐mg DA‐9701 (Motilitone, Dong‐A ST, Seoul, Korea) was taken three times per day before a meal for 24 days, and drug compliance was evaluated by checking the remaining tablets on the last day of the study. The dose was selected based on the findings of previous clinical studies . During the study period, patients were prohibited from taking laxatives, rescue medications for constipation, or other GI motility regulators.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the previous studies. 9,26 Another previous study reported that the complete symptom relief was achieved similarly by PPIs among the FD subgroups; ie, ulcer-like, dysmotility-like, reflux-like, and unspecified dyspepsia. 27 Further clinical investigations are urgently needed to assess the utility of FD subgroups defined by the Rome III criteria in clinical study and practice.…”
Section: Discussionmentioning
confidence: 99%
“…DA-9701 showed noninferior efficacy to itopride that is known to increase acetylcholine concentrations by inhibiting dopamine D 2 receptors and acetylcholinesterase. 17 Actually, itopride was reported to stimulate gastric motility and accelerate gastric emptying. 18 In several Asian countries such as South Korea and Japan, mosapride citrate (mosapride), a serotonin 5-HT 4 receptor agonist, as well as itopride has been used in patients with FD as a prokinetic drug.…”
Section: Discussionmentioning
confidence: 99%